Classification of knowledge in the Islamic civilization: from al-Ghazālī to al-Faṭānī - Muhammad Khatib Johari; Roziah Sidik @ Mat Sidek; Norshariani Abd Rahman; Abdul Latif Samian; Mohd Yusof Hj Othman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Intellectual discourse on classification of knowledge is a sub-topic in epistemology. In Islamic tradition, the philosophy of epistemology has its own uniqueness, besides being a distinguishing landmark in historical perspective between the Islamic and other civilizations. This study attempts to understand the concept of knowledge classification based on the perspectives of Abu Ḥāmid Muḥammad (hereafter mentioned as al-Ghazālī) (d. 1111CE) and Aḥmad bin Muḥammad Zayn (hereafter mentioned as al-Faṭānī) (d. 1908CE). In order to relate the purpose and objectives of knowledge to the Islamic Civilization, this study will identify the continuation of the idea on classification of knowledge in historical perspective. In addition, the comparison is to understand the connection between the classical knowledge classification in the Middle East to contemporary classification in the Malay World. Understanding al-Ghazālī’s perspective based on primary and secondary resources found that the general classification divided knowledge into two major categories, namely, ʿilm muʿāmalah (knowledge/science of transactions/proper conduct) and ʿilm mukāshafah (knowledge/science of unveiling). al-Faṭānī’s concept of classification was understood through his work entitled Fatāwā al-Faṭāniyyah which discussed 107 fatwas. Early content analysis of al-Faṭānī’s works showed that he indirectly followed the classification of knowledge conceived by al-Ghazali. This study is important to understand the role of knowledge as an essential foundation of the Islamic Civilization and its relevance to Islamization of contemporary knowledge.